Association between subcutaneous steroid injection for extravasation of vesicant anticancer drugs and skin ulcers requiring surgery. (June 2022) - Ohisa, Keiko; Yamana, Hayato; Morita, Kojiro; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
Abstract: Purpose: Although subcutaneous steroid injections are conventionally used to treat extravasation of vesicant anticancer drugs, their effects on the extravasation site remain unclear. We investigated the association between subcutaneous steroid injection in patients with extravasation of vesicant anticancer drugs and incidence of skin ulcers requiring surgery. Methods: We performed a retrospective cohort study using the Japanese Diagnosis Procedure Combination inpatient database. We identified patients with extravasation of vesicant anticancer drugs who were prescribed steroid ointment or cream on the same day as vesicant drug use between July 2010 and March 2019. The exposure group consisted of patients who had received subcutaneous steroid injections and local anesthetic in addition to topical steroids, whereas the control group had received topical steroids alone. The outcome was the incidence of skin surgical procedures during hospitalization. We performed a mixed-effect logistic regression analysis with random intercept for each hospital to compare outcomes between the groups. Results: We identified 7284 patients from 704 hospitals, including 3713 patients who had received topical steroids alone and 3571 who had received subcutaneous steroid injection in addition to topical steroids. According to mixed-effect logistic regression analysis, subcutaneous steroid injection was significantly associated with a higher incidence of skin surgery (odds ratio, 1.61; 95% confidence interval, 1.14–2.26; P = 0.007). Barthel Index, type of cancer, and type of vesicant drugs were also associated with surgery. Conclusions: Subcutaneous steroid injections after extravasation of vesicant anticancer drugs are associated with more frequent skin surgery. Randomized controlled trials are required to evaluate the safety and effectiveness of steroid injection. Highlights: Three percent of patients with extravasation required surgical treatment. Patients who received steroid injections had a higher incidence of skin ulcers. This is the first study to compare results with and without steroid injections. We adjusted for various patient covariates and conducted a mixed-effect analysis.